2020
DOI: 10.1002/jbm.b.34743
|View full text |Cite
|
Sign up to set email alerts
|

In vivo osseointegration and erosion of nacre screws in an animal model

Abstract: The use of resorbable devices for osteosynthesis has become a subject of interest. Nacre has been proposed as a resorbable and osteoconductive material favoring bone apposition without triggering an inflammatory reaction. We compared the in vivo osseointegration and erosion of nacre screws in an animal model with titanium screws. Implantation of similar nacre and titanium screws was performed in the femoral condyles of adult rats. Animals (n = 41) were randomized in four groups sacrificed at day one, 1, 6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The use of resorbable devices for osteosynthesis is an emerging area of focus. Nacre was shown to support bone apposition without triggering an inflammatory response [ 82 ]. It was also observed that giant cells and osteoclasts were present in bone grafted with nacre [ 83 ].…”
Section: Applicationsmentioning
confidence: 99%
“…The use of resorbable devices for osteosynthesis is an emerging area of focus. Nacre was shown to support bone apposition without triggering an inflammatory response [ 82 ]. It was also observed that giant cells and osteoclasts were present in bone grafted with nacre [ 83 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Nacre is a promising biomaterial in maxillofacial surgery [166]. Nacre has been proposed as a resorbable and osteoconductive material favouring bone apposition without triggering an inflammatory reaction [166], and it is biocompatible, non-toxic and biodegradable [131,156,166].…”
Section: Pharmacological Activity and Pharmaceutical Applicationsmentioning
confidence: 99%
“…[70] Nacre is biocompatible, non-toxic, biodegradable, osteogenic, and osteoconductive. [29,71,72] Nacre enhances tissue growth and bone tissue bonding. It also has excellent mechanical properties, such as Young modulus (30-40 GPa) and resistance to failure (185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200), that are similar to those of human bones (20 GPa and 140 MPa, respectively).…”
Section: Bioceramicsmentioning
confidence: 99%